An Ergonomic Intervention to Redesign Fish Smoking Device of Home Industry - Robert Hutagalung; Victor Oryon Lawalata; Nikmans Hattu (Jurnal Ilmiah Teknik Industri, 2022)
Smoke and heat become the contributors for increasing temperature and humidity in the production room, and workload of workers, and decreasing work productivity of a smoked fish home industry in Hative Kecil Village, Ambon City, Indonesia. This paper was aimed to redesign a fish smoking device with ergonomic consideration for solving the problem. An ergonomic intervention method applied to redesign the device. Redesign process describe result of ergonomic assessment in to the stages of rational method in order to produce new design. Despite the environmental variable (temperature and humidity), 10 male workers (age 40-50 year) were assessed their characteristics consisting of personal, anthropometric, workload and work productivity data. Final results presented a decreasing temperature (15.03%), humidity (8.06%), and workload of workers (75.89%) while work productivity increased 88.92%. It concluded that the device redesign can improve temperature, humidity, workload of workers and work productivity in the smoked fish home industry.